Toward more comprehensive and multi-modal transport evaluation. - Litman, Todd (My University, 2012)
This report critically evaluates transport policy and project evaluation practices, and describes ways to make them more comprehensive and multi-modal. The conventional transport planning paradigm is mobility-based, it assumes that the planning objective is to maximize travel speed and distance, and evaluates transport system performance based primarily on automobile travel conditions. A new paradigm recognizes that mobility is seldom an end in itself, the ultimate goal of most transport activity is accessibility, which refers to people s overall ability to reach desired services and activities. This new paradigm expands the range of objectives, impacts and options considered in the planning process. It recognizes additional costs from increased motorized transportation and more benefits from walking, cycling and public transport. More comprehensive and multi-modal planning is particularly important in large growing cities where increased motor vehicle traffic imposes particularly large costs, and in developing countries where a major portion of households cannot afford cars.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Verkehrsmittelwahl; Evaluation; Multimodalität; Mobilitätsverhalten; Verkehrsanalyse